Disconnect to recharge: Well-being benefits of digital disconnection in daily life - Gilbert, Alicia; Klingelhoefer, Julius; Meier, Adrian (2026)
Many aim to recalibrate and reduce their digital media use to improve well-being. We test the associations of digital disconnection with a set of positive, negative, and social indicators of well-being in a two-week experience sampling study. N = 237 participants reported on T = 12,407 situations in daily life. Results show that in situations in which participants disconnected more than usual, they reported higher affective well-being, energy, and social connectedness (within-person effects). In contrast, those who generally disconnected more than others reported no differences in well-being (between-person effects). Intrinsic motivation for disconnection positively moderated associations with affective well-being, energy, and social connectedness between persons. Disconnection was not related to stress, neither within nor between persons. The study further explores whether well-being effects differ depending on the aspects of digital media participants disconnected from. Overall, findings demonstrate how digital disconnection can achieve momentary – but not necessarily lasting – improvements in well-bein
https://cris.fau.de/converis/publicweb/Publication/335323869
Keywords: Digital disconnection; experience sampling; intrinsic motivation; media non-use; multilevel modelling; well-being